Perancangan Motion Graphic untuk Media Edukasi Bergaya Infografis sebagai Upaya Peningkatan Kesadaran Lingkungan pada Siswa SDN 52 Parupuk Tabing - Azzahra Putri Adilla; Wiki Lofandri (MASALIQ, 2026)
Although waste problems in the school environment require informative and engaging educational media, the development of infographic-style motion graphics tailored to the characteristics of elementary school students still requires further attention. This study aimed to design an infographic-style motion graphic as an educational medium concerning types of waste, their environmental impacts, and cleanliness-maintaining behaviors for students at SDN 52 Parupuk Tabing. The study employed a research and development approach with a design thinking framework comprising the empathize, define, ideate, prototype, and test stages. The participants consisted of 15–20 students from Grades II, IV, and V selected through convenience sampling, one teacher, and a media expert. Data were collected through observation, interviews, documentation, a literature review, and questionnaires, and were subsequently analyzed descriptively. The study produced a motion graphic entitled Jaga Lingkungan Yuk dari Sampah, with a duration of 3 minutes and 53 seconds, consisting of six scenes, presented in MP4 format and Full HD resolution, and integrating flat illustrations, two-dimensional animation, typography, narration, music, and sound effects. The expert evaluation indicated the need for revisions to the animation timing and transitions. These findings indicate that motion graphics can be developed as a communicative, engaging, and contextual supplementary medium for environmental education among elementary school students.